The relative age effect shifts students’ choice of educational track even within a school system promoting equal opportunities - Oterhals, Geir; Bachmann, Kari Elisabeth; Bjerke, Annette Hessen; Pedersen, Arve Vorland (Frontiers in Psychology, 2023)
In most education systems, the age of a given cohort of students spans up to 12 months, which creates a within-class age difference, or relative age effect, that tends to disadvantage younger students. Because birth month indeed correlates with academic performance, with poorer outcomes for students born later in the year, the effect can have lifelong consequences for students, whose academic performance justifies their acceptance into different educational tracks. Although past studies have identified the relative age effect in students’ choice of educational track in school systems in which students make such choices at the age of 10–14 years, we examined data from the Norwegian school system, in which education tracks are chosen at the age of 15–16 years. Our analysis of 28,231 applications to upper secondary school revealed a relative age effect in educational choices between academic and vocational tracks, such that younger students are significantly more likely to apply for vocational tracks, and the relative age effect is stronger for boys. Those findings have implications for actors involved in ensuring equity in education systems in Norway and elsewhere.